2021
DOI: 10.1186/s12936-021-03669-3
|View full text |Cite
|
Sign up to set email alerts
|

Vector incrimination and transmission of avian malaria at an aquarium in Japan: mismatch in parasite composition between mosquitoes and penguins

Abstract: Background Captive populations of penguins outside of their natural distributions are often maintained in outdoor facilities, such as zoos and aquariums. Consequently, such penguins in captivity are constantly exposed to mosquito vectors and risk of avian malarial infection during their active period from spring to autumn, which can be lethal to these naïve birds. Previous studies have investigated parasite prevalence in mosquitoes or penguins, but simultaneous investigations, which would be cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
2
0
2
Order By: Relevance
“…Differences in temporal distributions of the parasites in vectors and vertebrate host species can result in the absence of establishment of interactions among them. For example, Inumaru et al [ 32 ] investigated the prevalence of avian malaria and related haemosporidian parasites in both penguins and mosquitoes at an aquarium in northern Japan across multiple years, showing a mismatch in parasite composition between penguins and mosquitoes. Also, Gangoso et al [ 33 ] analyzed the parasite transmission network in an insular system formed by Eleonora's falcon ( Falco eleonorae ) as avian host, louse flies that parasitize the falcons as potential vectors and avian haemosporidians, showing a mismatch between the malaria lineages isolated in adult falcons and those found in louse flies.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in temporal distributions of the parasites in vectors and vertebrate host species can result in the absence of establishment of interactions among them. For example, Inumaru et al [ 32 ] investigated the prevalence of avian malaria and related haemosporidian parasites in both penguins and mosquitoes at an aquarium in northern Japan across multiple years, showing a mismatch in parasite composition between penguins and mosquitoes. Also, Gangoso et al [ 33 ] analyzed the parasite transmission network in an insular system formed by Eleonora's falcon ( Falco eleonorae ) as avian host, louse flies that parasitize the falcons as potential vectors and avian haemosporidians, showing a mismatch between the malaria lineages isolated in adult falcons and those found in louse flies.…”
Section: Introductionmentioning
confidence: 99%
“…Fokis et al (2008), reportó una menor incidencia de hemoparásitos en aves de hábitos urbanos y, aunque ambas especies llegan a compartir hábitat (Green et al, 2020), las ZENMAC capturadas para este estudio se distribuyeron hacia áreas más abiertas, con cuerpos de agua adyacentes, probablemente con más vectores (Lega et al, 2017;Lynton-Jenkins et al, 2020) y con mayor probabilidad de contagio (Hellard et al, 2016). La influencia de la estación del año (reproductiva) sobre la parasitemia pudiera ser considerada normal, al coincidir con la época de reproducción de los vectores (Inumaru et al, 2021) y eventos hormonales relevantes en la solución de la parasitemia por parte del hospedero aviar (Deviche & Parris, 2006). Aunque pueden existir diferencias regionales, Haemoproteus es el género hemoparasitario más común en aves, seguido por Plasmodium y Leucocytozoon (Carlson et al, 2013;Heym et al, 2019).…”
Section: Discussionunclassified
“…Este patrón se observó en este estudio a excepción del género Leucocytozoon, cuya ausencia podría estar asociada a las características altitudinales y climáticas del sitio de estudio que restringen la abundancia de los mosquitos y el desarrollo del parásito en estos vectores (Borji et al, 2011;Nath et al, 2014). Los resultados se traducen en que el sitio de estudio cuenta con una cantidad de vectores suficiente y capaz de transmitir hemoparásitos en ambas especies de aves (Valkiūnas & Iezhova, 2018;Inumaru et al, 2021). Los trabajos que analizan la parasitemia son limitados (Huang et al, 2020) y asocian este parámetro con el daño generado por el parásito al hospedero (Knowles et al, 2010;Muriel, 2020).…”
Section: Discussionunclassified
“…This is the case with the native honeycreepers of Hawai'i which were naïve to introduced avian malaria, leading to population decline and even the extinction of many native bird species ( Atkinson et al, 2013 ; Atkinson and Lapointe, 2009 ; LaPointe et al, 2012 ; Van Riper et al, 1986 ). Captive birds such as those in zoos and aviaries are also at high risk, as they may encounter haemosporidian parasites that they would not have encountered in their original distribution ( Inumaru et al, 2021 ; Lee et al, 2018 ; Olias et al, 2011 ; Scott, 1927 ; Vanstreels et al, 2016 ). Apart from those lethal effects, some studies have also reported negative associations between haemosporidian infection and host status, including both morphological and physiological effects.…”
Section: Introductionmentioning
confidence: 99%